Purification and characterization of a 1-deoxy-D-xylulose 5-phosphate synthase from Cymbopogon flexuosus - Kumar Gupta, Ashish; Ganjewala, Deepak (Acta Biologica Szegediensis, 2017)
Here we report purification and characterization of the enzyme 1-deoxy-D-xylulose 5-phosphate synthase (DXS) of the 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway from lemongrass (Cymbopogon flexuosus) leaves. The DXS catalyzes the condensation of pyruvate and glyceraldehyde 3-phosphate (G3P) to produce 1-deoxy-D-xylulose 5-phosphate (DOXP), which is the first and rate-limiting step of the MEP pathway. It is the main flux-controlling step and an attractive target to manipulate the formation of the MEP-derived products. The DXS was extracted from immature (15 days old) leaves of lemongrass cv. Suvarna and purified to homogenity using ion exchange DEAE column and gel filtration (Sephadex G-150) chromatography. The purified DXS was referred as CfDXS. The CfDXS had specific activity 8.56 U/mg. The Km values for the two substrates, pyruvate and G3P were 4.4 and 8.8 μM, respectively and for the cofactor TPP 62 μM. The Vmax of the CfDXS was 20 μmol/min. The optimum pH and temperature of the CfDXS were 7.5 and 40 °C, respectively. The CfDXS activity enhanced significantly in the presence of Mg2+ (1 mM), whereas affected moderately by Mn2+ and Zn2+ (1 mM each). The enzyme was purified upto 11.64 fold with an yield of 32.34%. Its molecular weight was 130 kDa. The DXS was quite stable and retaining more than 80% of the initial activity upon storage at 4 °C in 100 mM Tris-HCl buffer (pH 8) for one month.